Eligibility criteria for pediatric patients who may benefit from anti SARS-CoV-2 monoclonal antibody therapy administration: an Italian inter-society consensus statement - Marcello Lanari; Elisabetta Venturini; Luca Pierantoni; Giacomo Stera; Guido Castelli Gattinara; Susanna Maria Roberta Esposito; Silvia Favilli; Emilio Franzoni; Eleonora Fusco; Paolo Lionetti; Claudio Maffeis; Gianluigi Marseglia; et al. (BMC, 2022)
Abstract The fast diffusion of the SARS-CoV-2 pandemic have called for an equally rapid evolution of the therapeutic options. The Human recombinant monoclonal antibodies (mAbs) have recently been approved by the Food and Drug Administration (FDA) and by the Italian Medicines Agency (AIFA) in subjects aged ≥12 with SARS-CoV-2 infection and specific risk factors. Currently the indications are specific for the use of two different mAbs combination: Bamlanivimab+Etesevimab (produced by Eli Lilly) and Casirivimab+Imdevimab (produced by Regeneron). These drugs have shown favorable effects in adult patients in the initial phase of infection, whereas to date few data are available on their use in children. AIFA criteria derived from the existing literature which reports an increased risk of severe COVID-19 in children with comorbidities. However, the studies analyzing the determinants for progression to severe disease are mainly monocentric, with limited numbers and reporting mostly generic risk categories. Thus, the Italian Society of Pediatrics invited its affiliated Scientific Societies to produce a Consensus document based on the revision of the criteria proposed by AIFA in light of the most recent literature and experts' agreement. This Consensus tries to detail which patients actually have the risk to develop severe disease, analyzing the most common comorbidities in children, in order to detail the indications for mAbs administration and to guide the clinicians in identifying eligible patients.